Schlieren Measurements of Fine Scale Mixing - Zakanycz, S.; Brodkey, R.S. (Engineering Transactions, 1976)
The present paper considers Schlieren measurements of fine scale mixing in a similar system as used by Mc Kelvey et al. [1]. A unique experiment using the Toepler-Schlieren apparatus was. performed so to obtain quantitative mixing data for the mixing of individual air jets with helium jets.